PENGARUH DARI NILAI PELANGGAN, KUALITAS PELAYANAN DAN KOMUNIKASI TERHADAP KEPUASAN PELANGGAN DAN DAMPAKNYA TERHADAP LOYALITAS PELANGGAN PADA PENGGUNA PROVIDER TELKOMSEL (STUDI PADA MAHASISWA UNISBANK - Intan Ambar Rezti, 10.05.51.0074; Marlien, Marlien (Students Journal of Economic and Management, 2014)
Customer is one of the most important elements in the establishment of an enterprise. Its existence must be considered, one of the issue of concern within the company is how to create customer loyality. Efforts to provide security for customer loyalty, it can be done by creating customer satisfaction. The purpose of this research is : To analyze the effect of customer value on user satisfaction provider telkomsel. To analyze the effect of service quality on user satisfaction provider telkomsel. To analyze the effect of communication on user satisfaction provider telkomsel. The population in this study is the provider telkomsel users in the city of Semarang. By making use of purposive sampling technique, the sample in this study were 150 students of stikubank university. Type of data used are primary data, by using the method of collecting data through questionnaires. The analysis tool is regression analysis.The result of the study are : customer value positife effect on customer satisfaction, customer value means that if the increases, the satisfaction will increase. Service quality has positive influence on customer satisfaction, means that if the service quality increases, the satisfaction will increase. Communication has positive effect on customer satisfaction, means that if the communication increases, the satisfaction will increase. Customer satisfaction has positive influence on customer loyalty, customer satisfaction means that if increases, the loyalty will increase.Keywords : Customer Value, Service Quality, Communication, Customer Satisfaction, Customer Loyalty.